Caracterização de genes do vírus do ectima contagioso envolvidos na regulação da via de sinalização do NF-κB - Diel, Diego Gustavo (2010)
Orf virus (ORFV), the type member of the genus Parapoxvirus of the family Poxviridae, is the etiologic agent of orf or contagious ecthyma, a contagious and ubiquitous disease of sheep and goats. ORFV genome consists of a double stranded DNA molecule with approximately 138 Kb, and contains 131 putative genes. Among those, 15 are novel genes, unique to parapoxviruses, which lack homology to other known viral or cellular genes. In the present study we describe the functional characterization of three of these genes, ORFV024, ORFV002, and ORFV121. Results presented here demonstrate that the proteins encoded by these genes inhibit the activation of the nuclear factor-kappa B (NF-κB) signaling pathway. ORFV-encoded ORFV024 inhibits activation of the NF-κB signaling pathway in the cell cytoplasm by inhibiting phosphorylation of the IκB kinases, IKKα and IKKβ, consequently inhibiting the activation of the IKK complex. Deletion of ORFV024 from the ORFV genome had no significant effect on disease severity, progression or time to resolution in sheep, indicating that ORFV024 does not contribute to ORFV virulence. ORFV-encoded ORFV002 functions in the cell nucleus, where it interacts with the NF-κB subunit NF-κB-p65, inhibiting its acetylation, a p300-mediated modification of NF-κB-p65 which modulates its transcriptional activity. Similarly to ORFV024, deletion of ORFV002 from the ORFV genome had no significant effect on ORFV virulence and disease pathogenesis in sheep. ORFV-encoded ORFV121 functions in the cell cytoplasm, where it binds to and inhibits phosphorylation and nuclear translocation of NF-κB-p65. Deletion of ORFV121 from the ORFV genome resulted in a marked attenuated disease phenotype in sheep, indicating that ORFV121 is a determinant of virulence of ORFV in the natural host. These results indicate that ORFV, like other poxviruses, has evolved multiple strategies to modulate NF-κB, targeting different steps of the signaling pathway. Results obtained in the pathogenesis studies performed here suggest that multiple NF-κB inhibitors encoded by ORFV may exert complementary and/or redundant functions to effectively block host cell responses regulated by the NF-κB signaling pathway. Additionally, it is possible that ORFV-encoded NF-κB inhibitors modulate distinct cellular processes regulated by NF-κB in vivo. A better understanding of ORFV-host interactions may provide valuable insights for the development of improved vaccines against orf, or yet for the development of novel ORFV-based therapeutic agents and vaccine vectors with enhanced safety and efficacy, and a broader applicability.